A sodium ion battery positive electrode material and preparation method thereof
The P2-Na0.67Ni0.33Fe0.33Mn0.33O2 material was prepared by solid phase method and lithium doped, which solved the problem of insufficient cycle stability and rate performance of sodium ion batteries and achieved efficient electrochemical performance.
Patent Information
- Application Number
- CN202410121936.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-29
- Publication Date
- 2025-04-04
AI Technical Summary
Existing sodium ion batteries have problems with insufficient cycle stability and rate performance.
The P2-Na0.67Ni0.33Fe0.33Mn0.33O2 material was prepared by solid phase method and lithium doped to study the influence of different sodium and lithium sources on the microstructure and electrochemical properties of the sample, and determine the best process parameters.
It realizes the high cycle stability and rate performance of the positive electrode material of sodium ion battery, and is suitable for high voltage and high rate charging and discharge environments, and can quickly charge and short charging time.
Smart Images

Figure CN119764434A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a battery preparation technology, in particular to a sodium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] The research on high-performance lithium-ion batteries and their electrode materials is a hot topic in the fields of electrochemistry, material chemistry, physics and other scientific and technological fields, as well as in the fields of power and energy storage battery industry. There are currently a variety of technical routes for large-scale electrochemical energy storage technology, among which lithium-ion batteries have become one of the important technical routes due to their high energy density, high power density and long cycle life. However, as lithium-ion batteries are increasingly used in power vehicles, the demand for lithium will increase greatly. In nature, the reserves of lithium are very limited, accounting for about 0.006% in the bottom shell, and the distribution is uneven. Its development will become increasingly difficult and the development cost will also increase greatly. This may become an important issue in the future for the development of long-life secondary batteries for large-scale power and energy storage.
[0003] Compared with lithium-ion batteries, the natural abundance and wide distribution of sodium resources have attracted widespread attention to sodium-ion batteries. The research and development of sodium-ion batteries can, to a certain extent, alleviate the problem of limited battery development caused by the shortage of lithium resources. Sodium-ion batteries have the advantages of good renewability, low cost and high capacity. The positive electrode material is one of the most important components of the battery. If excellent, safe and stable materials are developed on this basis, sodium-ion batteries will have greater market competitive advantages than lithium-ion batteries. Therefore, the sodium-ion positive electrode material industry has good development prospects. By overcoming challenges, seizing opportunities and taking advantage of favorable factors, the sodium-ion battery positive electrode material industry is expected to achieve sustained and stable development. Among the many sodium-ion battery positive electrode materials, layered transition metal oxide positive electrode materials have become a hot research field due to their high energy density.
[0004] The working principle of sodium ion battery is similar to that of lithium ion battery. The positive electrode material is sodium ion, the negative electrode is made of hard carbon active material that can be more easily embedded and de-embedded, and the electrolyte is composed of sodium ion solution in organic solvent or water. Polyanion, Prussian blue, oxide materials, especially layered Na x MO2 (M = Fe, Mn, Co, V, Ti) and its binary and ternary materials show good charge-discharge specific capacity and cycle stability. At the same time, in the same main group of the periodic table, sodium and lithium have similar physical and chemical properties. According to the different positions of sodium ions in the cell, transition metal layered oxides Na x MO2 (M = metal ion) can be divided into P2 type (prismatic interstitial Na + , AB-BA enriched) and O3 type (octahedral interstitial Na+ , ABC-ABC enrichment). Compared with the single-phase crystal structure of O-type or P-type, the P2 and O3 phases have different stable structures. Among them, the interlayer spacing of the P2 structure is larger, and Na + It is easy to diffuse and has high ion conductivity. The O3 structure has more octahedral voids as intercalation sites for sodium ions, so it has a higher capacity. Based on this, it is particularly important to develop high-performance and high-stability layered oxide materials for sodium ion batteries, improve the energy density, rate performance, low-temperature performance, cycle life and safety performance of sodium batteries, and promote the development of sodium ion battery technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of insufficient cycle stability and rate performance of existing sodium ion batteries, to provide a sodium ion battery positive electrode material and a preparation method thereof, to prepare P2-Na by a solid phase method 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 material, and then doped with lithium to study the effects of different sodium and lithium source contents on the sample Li x Na 1- x Ni 0.33 Fe 0.33 Mn 0.33 The influence of the microstructure and electrochemical properties of the O2 cathode material was used to determine the optimal process parameters.
[0006] The specific plan is as follows:
[0007] A sodium ion battery positive electrode material, the sodium ion battery positive electrode material is a P2 type layered oxide, and its chemical formula is Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, where x = 3% - 3.5%.
[0008] Furthermore, the initial discharge specific capacity of the sodium ion battery positive electrode material is 140-145 mAh·g -1 .
[0009] Furthermore, the sodium ion battery positive electrode material was subjected to constant current charge and discharge test, and voltage platforms appeared at 3.7V and 3.3V.
[0010] Furthermore, the sodium ion battery positive electrode material has a capacity retention rate of 99.0-99.5% after 120 cycles at a voltage window of 2-4V and a rate of 0.1C.
[0011] Furthermore, the capacity retention rates of the sodium ion battery positive electrode material after 20 cycles at 0.1C, 0.5C, 1C, 3C, 5C, and 10C are independently 98.5-99.5%.
[0012] The present invention also provides a method for preparing the positive electrode material of a sodium ion battery, comprising the following steps:
[0013] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as raw material and dry ball milled in a pot mill to obtain a mixed material;
[0014] S2, calcining the mixture in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0015] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 The O2 positive electrode material and the lithium source are mixed and calcined to obtain the sodium ion battery positive electrode material.
[0016] Furthermore, the ball milling time in S1 was 2–12 h;
[0017] Optionally, the calcination temperature in S2 is 800-900° C., and the calcination time is 6-12 h.
[0018] Furthermore, the lithium source in S3 is at least one of lithium carbonate, lithium hydroxide, lithium oxalate, and lithium nitrate;
[0019] Optionally, the calcination temperature in S3 is 800-1000° C. and the calcination time is 6-20 h.
[0020] The present invention also protects a sodium ion battery positive electrode, comprising the sodium ion battery positive electrode material.
[0021] The present invention also protects a sodium ion battery, comprising the sodium ion battery positive electrode.
[0022] Beneficial effects: The sodium ion battery positive electrode material of the present invention has a typical P2 crystal structure, a high first discharge capacity, and good cycle stability and rate performance. It is suitable for high voltage and high rate charge and discharge environments, can achieve fast charging, and has a short charging time, and has excellent market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solution of the present invention, the following will briefly introduce the drawings. Obviously, the drawings in the following description only relate to some embodiments of the present invention, but are not intended to limit the present invention.
[0024] Figure 1 This is one of the SEM images of the sodium ion battery positive electrode material provided by one embodiment of the present invention;
[0025] Figure 2 This is the second SEM image of the sodium ion battery positive electrode material provided by one embodiment of the present invention;
[0026] Figure 3 This is the third SEM image of the sodium ion battery positive electrode material provided by one embodiment of the present invention;
[0027] Figure 4 This is the fourth SEM image of the sodium ion battery positive electrode material provided by one embodiment of the present invention;
[0028] Figure 5 This is a constant current charge and discharge curve of a sodium ion battery positive electrode material provided by an embodiment of the present invention;
[0029] Figure 6 This is a cyclic voltammetry curve of a positive electrode material for a sodium ion battery provided by an embodiment of the present invention;
[0030] Figure 7 This is a rate performance diagram of a sodium ion battery positive electrode material provided by an embodiment of the present invention after 20 cycles at 0.1C, 0.5C, 1C, 3C, 5C, and 10C. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. In the examples, those without specifying specific techniques or conditions are carried out according to the techniques or conditions described in the literature in this area or according to the product specification. Those without specifying the manufacturer of reagents or instruments used are all conventional products that can be obtained commercially. In the following examples, if not clearly stated, "%" refers to weight percentage.
[0032] The test methods used below include:
[0033] Battery performance test: At room temperature, the positive electrode materials prepared in the embodiments and comparative examples are taken as active materials, and the slurry is prepared according to the mass ratio of active material: binder: conductive agent = 8:1:1, wherein the binder is polyvinyl alcohol and the conductive agent is graphite. After baking, the pole piece is obtained, and then metallic sodium is used as the counter electrode, and the sodium ion battery electrolyte (polyfluoride sodium ion battery electrolyte) is used as the electrolyte, and the button battery is assembled under a vacuum environment. The electrochemical performance of the button battery, including constant current charge and discharge (GCD), cycle stability and rate performance. Among them, the main conditions of constant current charge and discharge (GCD) include 0.1C charge and discharge at room temperature; the main conditions of cycle stability include 1C charge and discharge at room temperature (the capacity retention rate is less than 80% to complete the test); the main conditions of rate performance include 0.1C charge at room temperature, 0.1C, 0.2C, 0.5C, 1C, 5C, 10C discharge.
[0034] Example 1
[0035] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0036] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as the raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0037] S2, calcining the mixture at 800°C for 10 h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0038] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and lithium carbonate are mixed, and the raw material dosage is based on the target chemical formula of Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, wherein x=2%, is calcined at 850° C. for 10 h to obtain the sodium ion battery positive electrode material.
[0039] Example 2
[0040] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0041] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn0.33 (OH)2 was used as the raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0042] S2, calcining the mixture at 800°C for 10 h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0043] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and lithium carbonate are mixed, and the raw material dosage is based on the target chemical formula of Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, wherein x=2.5%, is calcined at 850° C. for 10 h to obtain the sodium ion battery positive electrode material.
[0044] Example 3
[0045] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0046] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as the raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0047] S2, calcining the mixture at 800°C for 10 h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0048] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and lithium carbonate are mixed, and the raw material dosage is based on the target chemical formula of Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, wherein x=3%, is calcined at 850° C. for 10 h to obtain the sodium ion battery positive electrode material.
[0049] Example 4
[0050] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0051] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0052] S2, calcining the mixture at 800°C for 10 h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0053] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and lithium carbonate are mixed, and the raw material dosage is based on the target chemical formula Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, wherein x=3.5%, is calcined at 850° C. for 10 h to obtain the sodium ion battery positive electrode material.
[0054] Example 5
[0055] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0056] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0057] S2, calcining the mixture at 800°C for 10 h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0058] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and lithium carbonate are mixed, and the raw material dosage is based on the target chemical formula Li x Na 1-x Ni 0.33 Fe 0.33 Mn0.33 O2, wherein x=4%, is calcined at 850° C. for 10 h to obtain the sodium ion battery positive electrode material.
[0059] Example 6
[0060] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0061] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as the raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0062] S2, calcining the mixture at 900°C for 10 h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0063] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material and lithium carbonate are mixed, and the raw material dosage is based on the target chemical formula of Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, wherein x=3.5%, is calcined at 800° C. for 20 h to obtain the sodium ion battery positive electrode material.
[0064] Example 7
[0065] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0066] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as the raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0067] S2, calcining the mixture at 850°C for 12h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material;
[0068] S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn0.33 O2 positive electrode material and lithium carbonate are mixed, and the raw material dosage is based on the target chemical formula Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, wherein x=3.5%, is calcined at 1000° C. for 6 h to obtain the sodium ion battery positive electrode material.
[0069] Comparative Example 1
[0070] A method for preparing a positive electrode material for a sodium ion battery comprises the following steps:
[0071] S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as raw material and dry ball milled in a pot mill for 8 h to obtain a mixed material;
[0072] S2, calcining the mixture at 800°C for 10 h in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 positive electrode material, as a positive electrode material for sodium ion batteries, namely Li x Na 1- x Ni 0.33 Fe 0.33 Mn 0.33 O2, where x=0%.
[0073] Performance Testing
[0074] The sodium ion battery positive electrode material prepared in Example 4 was taken for morphology detection. Figure 1-Figure 4 As shown in the figure, we can see that the particles are spherical, about 10-30 microns, evenly distributed in size, with clear surface texture, and are composed of multiple elements such as nickel, iron, manganese, sodium, and lithium.
[0075] The constant current charge and discharge test results of the positive electrode material of sodium ion battery are shown in Figure 5 The initial discharge specific capacities of the six groups of samples (x = 0%, 2%, 2.5%, 3%, 3.5%, 4%) are 119.1, 138.8, 142.2, 142.7, 137.6 and 139.9 mAh g -1. When x=3.5%, the capacity retention rate is the best, which is 99.23% after 120 cycles at a voltage window of 2-4V and a rate of 0.1C. The x=2% and x=2.5% samples show poor cycle stability due to the formation of sodium-deficient compounds. The capacity retention varies with the sodium source content. When x=3.5%, the capacity retention rate is higher. However, the sodium source content in the x=4% sample exceeds the standard, which deteriorates its cycle. This is because electrically insulating NaOH and Na2CO3 are formed on the surface of the electrode material during the cycle.
[0076] The cyclic voltammetry test results of sodium ion battery positive electrode materials are shown in Figure 6 The multiple redox peaks in the cyclic voltammetry curve correspond well to the multiple voltage platforms in the constant current charge-discharge curve. The voltage platform below 3V can be attributed to Mn 3+ / Mn 4+ Redox couple. 3.7V and 3.3V voltage platforms with Ni 3+ / Ni 4+ and Ni 2+ / Ni 3+ related to the redox reaction.
[0077] The test results of the cycle stability and rate performance of the positive electrode materials for sodium ion batteries are shown in Figure 7 ,From the test results, the sample was cycled 20 times at 0.1C, 0.5C, 1C, 3C, 5C, and 10C. The capacity retention rate of the sample with x=3.5% at different rates was better than that of other samples, which were 99.23%, 99.18%, 99.05%, 98.89%, 98.78%, and 98.67%, respectively, which was consistent with the capacity retention rate results of the cycle performance test. This can be attributed to the fact that under the appropriate sodium source content, neither sodium defect compounds nor electrical insulating materials appeared on the surface. Therefore, when x=3.5%, the sample has the best cycle stability and rate performance.
[0078] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0079] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0080] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery is a P2-type layered oxide, whose chemical formula is Li x Na 1-x Ni 0.33 Fe 0.33 Mn 0.33 O2, where x = 3% - 3.5%.
2. The sodium ion battery positive electrode material according to claim 1, characterized in that: The initial discharge specific capacity of the sodium ion battery positive electrode material is 140-145 mAh·g -1 .
3. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The sodium ion battery positive electrode material was subjected to constant current charge and discharge test, and voltage platforms appeared at 3.7V and 3.3V.
4. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The sodium ion battery positive electrode material has a capacity retention rate of 99.0-99.5% after 120 cycles at a voltage window of 2-4V and a rate of 0.1C.
5. The sodium ion battery positive electrode material according to claim 1 or 2, characterized in that: The capacity retention rates of the sodium ion battery positive electrode material after 20 cycles at 0.1C, 0.5C, 1C, 3C, 5C and 10C are independently 98.5-99.5%.
6. The method for preparing the positive electrode material for a sodium ion battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, with Na2CO3, Ni 0.33 Fe 0.33 Mn 0.33 (OH)2 was used as raw material and dry ball milled in a pot mill to obtain a mixed material; S2, calcining the mixture in an air atmosphere to obtain P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 O2 cathode material; S3, the P2-Na 0.67 Ni 0.33 Fe 0.33 Mn 0.33 The O2 positive electrode material and the lithium source are mixed and calcined to obtain the sodium ion battery positive electrode material.
7. The method for preparing the positive electrode material for a sodium ion battery according to claim 6, characterized in that: The ball milling time in S1 is 2-12 h; Optionally, the calcination temperature in S2 is 800-900° C., and the calcination time is 6-12 h.
8. The method for preparing the positive electrode material for sodium ion batteries according to claim 6 or 7, characterized in that: The lithium source in S3 is at least one of lithium carbonate, lithium hydroxide, lithium oxalate and lithium nitrate; Optionally, the calcination temperature in S3 is 800-1000° C. and the calcination time is 6-20 h.
9. A sodium ion battery positive electrode, comprising the sodium ion battery positive electrode material according to any one of claims 1 to 5.
10. A sodium ion battery comprising the sodium ion battery positive electrode according to claim 9.